Macro's missing link the unbridged gap between Monetarism and the Wicksell Connection - David E. W. Laidler (The University of Western Ontario, Department of Economics, 2023)
Modern mainstream macroeconomics treats the economy 'as if' always in equilibrium. Two older traditions, Monetarism and the Wicksell Connections have always dissented, arguing that how agents gather information and apply it to the co-ordination of their activities are prior problems requiring attention before equilibrium can, or cannot, be assumed. They have developed the implications of this claim along different lines, however, with the former dealing with questions raised by the existence of monetary exchange in general and the latter concentrating in particular on inter-temporal issues. This gap has persisted since Wicksell opened it up, and has never been satisfactorily bridged: why?
Keywords: B13; B22; D50; D80; E10; 330; Wicksell; Monetarism; information; co-ordination; equilibrium